1997
DOI: 10.1097/00003072-199701000-00004
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Value of Tc-99m Human Polyclonal Immunoglobulin Imaging Compared to Tc-99m HMPAO Labeled Leukocytes in Inflammatory Bowel Disease

Abstract: The aim of this study was to establish the usefulness of Tc-99m human polyclonal immunoglobulin (HIG) imaging in a group of patients who were suspected of having inflammatory bowel disease (IBD). The authors performed 30 scans (15 with Tc-99m HMPAO leukocytes and 15 with Tc-99m HIG) on 15 patients with IBD. Ten patients had Crohn's disease and five had ulcerative colitis. The sensitivity of Tc-99m HIG scintigraphy for detecting IBD was 33%, while the sensitivity of Tc-99m HMPAO leukocyte imaging was 100%. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 13 publications
0
1
0
2
Order By: Relevance
“…Bereits frühzeitig wurden 99 111 In-HIG) wurde in der Vergangenheit für die Entzündungsdiagnostik eingesetzt [30,108]. Basierend auf der problematischen Gewinnung der Ausgangssubstanz aus gepooltem Plasma haben diese Radiopharmazeutika heute keine Bedeutung mehr, obwohl der Anreicherungsmechanismus, wenigstens bei 111 In-HIG, über die Dissoziation und Retention des Nuklids im entzündlichen Herd durchaus spezifische Aspekte aufwies [155].…”
Section: Tc-nanokolloidunclassified
“…Bereits frühzeitig wurden 99 111 In-HIG) wurde in der Vergangenheit für die Entzündungsdiagnostik eingesetzt [30,108]. Basierend auf der problematischen Gewinnung der Ausgangssubstanz aus gepooltem Plasma haben diese Radiopharmazeutika heute keine Bedeutung mehr, obwohl der Anreicherungsmechanismus, wenigstens bei 111 In-HIG, über die Dissoziation und Retention des Nuklids im entzündlichen Herd durchaus spezifische Aspekte aufwies [155].…”
Section: Tc-nanokolloidunclassified
“…Im ersten Fall ist der Ausschluss der entzündlichen Darmerkrankung bei Patienten mit persistierenden Diarrhöen wichtig, im zweiten ist der Ansatz mehr geeignet, um die Ausbreitung der Erkrankung bei Patienten zu definieren, von denen man weiû, dass sie eine entzündliche Darmerkrankung haben. Viele Direktvergleiche zwischen Tc-99m-Leukozytenszintigraphie und Immunszintigraphie wurden in der Literatur veröffentlicht, aber generell waren die Ergebnisse enttäuschend, besonders die Vergleiche zwischen polyklonalen Antikörpern [32,33,45] und monoklonalen Antikörpern mit Leukozyten [40, 46 ± 50]. Die Leukozytenszintigraphie ist besonders nützlich bei Morbus Crohn, da hierdurch Entzündungsherde im gesamten Gastrointestinaltrakt diagnostiziert werden können.…”
Section: Klinischer Einsatz Der Leukozytenszintigraphie Bei Entzündliunclassified
“…One study showed that the 99m Tc HMPAO leukocyte scan had 95% sensitivity and 100% specificity in detecting active Crohn's disease (CD) (11). A more recent study similarly showed that 99m Tc HMPAO leukocyte imaging was 100% sensitive in detecting patients with active CD and ulcerative colitis (UC) (12). At our center, the James Whitcomb Riley Hospital for Children in Indianapolis, Indiana, U.S.A., 99m Tc HMPAO is used by the Nuclear Medicine Department to detect active intestinal inflammation.…”
mentioning
confidence: 99%